A computational model for failure of ductile material under impact. (October 2017) - Islam, Md Rushdie Ibne; Chakraborty, Sukanta; Shaw, Amit; Reid, Stephen
Highlights: SPH based computational framework is developed for modelling ductile failure under impact. Crack propagation is modelled through pseudo-spring strategy. Adiabatic shear plugging in metal plate is studied through the developed framework. Predicted results are compared with experimental observations reported in the literature. Abstract: In addition to an accurate mathematical representation of the material, a computational modelling method for assessing impact problems involving large plastic deformation, damage localization, fracture etc. requires a suitable discretization scheme which can simulate the relevant physical processes without introducing any numerical artifact or being unstable. In this paper, a computational framework based on Smoothed Particle Hydrodynamics (SPH) is presented for studying the deformation and failure of ductile material, steel plate, under impact loading. This provides a useful design tool to simulate penetration of the plate. Crack propagation is modelled through a pseudo spring analogy wherein the interacting particles are assumed to be connected through pseudo-springs and the interaction is continuously modified through an order-parameter based on the accumulated damage in the spring. At the onset of crack formation i.e., when the accumulated damage reaches the critical value, the spring breaks which results in termination of interaction between particles on either sides of the spring. A key feature of the computational model is that it can capture arbitrary propagating cracks without introducing any special treatment such as discontinuous enrichment, particle-splitting etc. This computational framework is used herein to study adiabatic shear plugging in metal plates when modelling penetration under impact loading by a flat-ended, cylindrical projectile. The effects of different damage criteria are discussed. Computed results are compared with the experimental observation given in the literature and the efficacy of the framework is demonstrated.